The clinic surgeon as the main link in the treatment of patients with chronic ischemia of the lower extremities of atherosclerotic genesis - Yu. V. Chervyakov; I. A. Moskovskiy (Амбулаторная хирургия)
Introduction. An alternative way in the treatment of intermittent claudication is the use of genetic engineering technologies that lead to the stimulation of their own vasculogenesis in ischemic limbs. Treatment is carried out on an outpatient basis.Purpose: to present the results of complex conservative treatment using a drug based on a plasmid with the VEGF165 gene in patients with grade II CINI according to the Fontaine – A.V. Pokrovsky classification for 7 years after one course of gene therapy.Materials and methods. From 2009 to 2015, 50 patients were treated. Men – 41, women – 9. Average age 64.3 ± 10.5 years. All patients received basic therapy for atherosclerosis. In addition, a 1.2 mg gene preparation was injected twice into the muscles of the ischemic limb. The preservation of the limb, the survival rate of patients, the change in the distance of painless walking according to the treadmill test were assessed.Results and discussion. The safety of the limb after 7 years was 94%, the survival rate was 80%. Significant and moderate clinical improvement was noted in 68% of cases, satisfactory result – 6%, deterioration – 2% of patients. Only in 6% of cases there was an unfavorable outcome associated with the progression of chronic limb ischemia. All patients showed good tolerance to the drug and no side effects. Continuous conservative treatment of patients with peripheral atherosclerosis is the key factor preventing rapid progression of the disease. There is high requirement for the development of new areas of the combination treatment, which would lead to compensation of blood circulation in the extremities in peripheral atherosclerosis. The provided innovative treatment method with widespread introduction into outpatient practice will improve the quality of life of patients with intermittent claudication.Conclusions. Long-term results of treatment of patients with grade II CINI using gene therapy have been demonstrating high efficiency for 7 years. The presented innovative method of treatment, with its widespread introduction into outpatient practice, will improve the quality of life of patients with intermittent claudication by increasing the passable distance without pain in the legs, reduce the risk of ischemia progression, and minimize the burden on the healthcare system.